IMPROVING STUDENT LEARNING OUTCOMES BY USING THE NUMBERED HEAD TOGETHER (NHT) LEARNING MODEL IN THE SUBJECTS OF THE APPLICATION OF ELECTRONIC CIRCUITS (PRE) KELAS XI TAV SMK NEGERI 1 MANDAU TAHUN PELAJARAN 2019 / 2020 - Irda Nelli (Ensiklopedia of Journal, 2021)
This study aims to improve students' learning outcomes in the subjects of Electronic Circuit Application with the learning model "Numbered Head Together (NHT)" in students of SMK Negeri 1 Mandau. The subjects of the study were students of grade XI AV SMK Negeri 1 Mandau Year 2019 / 2020 a total of 27 students. This research is a Class Action Research consisting of two cycles consisting of planning, action, observation, and reflection stages. Before cycle 1 learning is carried out conventionally and in cycles 1 and 2 learning is carried out with the Numbered Head Together (NHT) model. During the implementation of the Numbered Head Together (NHT) learning model, student learning outcomes and learning activities are observed and analyzed by teachers and assisted by other teachers as observers. The results showed that with the numbered head together (NHT) learning model can significantly improve student learning outcomes. This can be seen from the increase in the average grade of students who were originally 61.29 to 72.96 in cycle 1 and in cycle 2 to 88.88. Students' creativity and motivation also appear to increase as found in the observation sheet.